Characteristics and prognosis of stage I-III breast cancer subtypes in Brazil: The AMAZONA retrospective cohort study. (April 2019) - Simon, Sergio Daniel; Bines, José; Werutsky, Gustavo; Nunes, João Soares; Pacheco, Fernando Chalu; Segalla, José Getúlio; Gomes, Andrea J.S.; Adam Van Eyll, Brigitte Marie H.R.; Gimenes, Daniel Luiz; Crocamo, Susanne; Freitas-Junior, Ruffo; Lago, Lissandra Dal; et al.
Abstract: Objective: To describe stage I-III breast cancer (BC) molecular subtypes and outcomes among a cohort of patients from Brazil. Methods: AMAZONA study is a retrospective cohort conducted from June 2008 to January 2009 including women of at least 18 years old, with histologically proven breast cancer, diagnosed in 2001 (n = 2198) and 2006 (n = 2714). In this analysis, we included patients who underwent surgery, had stage I-III disease and available pathological information (n = 2296). We estimated molecular subtypes by local immunohistochemical stains. Data was obtained from medical charts and public databases. Results: Mean age at diagnosis was 54 years and 41.1% were younger than 50 years. 23.3% were diagnosed in stage I, 53.5% in stage II and 23.2% in stage III. 80.8% were treated in the public health system. 71.3% had hormonal receptor positive disease, 15.7% were HER-2 positive and 21.1% had triple-negative breast cancer. 55.6% were treated with mastectomy and 96.2% received adjuvant treatment (82.2% chemotherapy). 13.4% of HER-2 positive patients received adjuvant trastuzumab. Overall survival rate at 5 years was 96.84% for stage I, 94.16% for stage II and 70.48% for stage III. Molecular subtypes were independent prognostic factor in stages II and III patients. Conclusions: Brazilian women have a higher risk of being diagnosed with late stage breast cancer and younger age than in high-income countries. Luminal-like disease is the most common molecular subtype in the country. Triple negative and HER-2 positive had the worst prognosis. Highlights: A high proportion of patients are diagnosed with breast cancer under 50 years old in Brazil. Brazilian women have a higher risk of being diagnosed with locally advanced breast cancer. More than 70% are luminal like breast cancer. Common immunohistochemical stains create distinct groups with different prognosis.